Mental health promotion competencies in the health sector based on a Delphi study. Issue 6 (5th November 2018) - Tamminen, Nina; Solin, Pia; Kannas, Lasse; Linturi, Hannu; Stengård, Eija; Kettunen, Tarja
Abstract : Purpose: Effective public mental health policy and practice call for a trained workforce that is competent in mental health promotion and delivering on improved mental health. Systematic information on what competencies are needed for mental health promotion practice in the health sector is lacking. The purpose of this paper is to investigate these competencies for mental health promotion. Design/methodology/approach: A Delphi survey was carried out to facilitate a consensus-building process on development of the competencies. Professionals ( n =32) working in mental health and mental health promotion took part in the survey. The experts were asked their professional views on the needed competencies as well as to rank the importance of the competencies. Two questionnaire rounds were carried out in order to reach consensus. Findings: In total, 16 main competencies and 56 subcompetencies were identified through the Delphi survey. The competencies were divided into three category domains: theoretical knowledge, practical skills and attitudes and values each category representing an important aspect of mental health promotion competency. Practical implications: The competencies provide a resource for workforce development, as they illustrate what theoretical knowledge, practical skills and attitudes and values are required. They provide an instrument to enhance education and training programmes in mental health promotion contributing to a more skilled workforce and improved quality of practice as well. Originality/value: A strong consensus was reached within the participating experts, them viewing all competencies as important. The identified competencies highlight the great variety of different competencies and competency areas that are needed for effective mental health promotion practice in the health sector.